Notas acerca de la "Tetragamia" de León VI, el sabio - Ossandón Widow, María E. (Byzantion Nea Hellás, 2015)
The Bizantine emperor Leo VI, who reigned between 866 and 912 AD was a disciple of Focius and acquired a great classic culture, as well as an almost enciclopedic knowledge. He also was a compassionate man, but in hisprivate life he was not very lucky. He became widower three consecutivetimes. After the death of his third wife, he gol married once again. The churchdid not accept that, since it was not allowed to gel married after the spouse' sdeath. On the other hand, divorce was permitted by the civil law. This factitself was a contradiction, for divorce is a dissolved bond. In widowhood, thelink has finished sin ce one of the spouses has died.The authoress studies the difficulties caused by the second and third Leon's marriages, and the legislation dictated by him, which allowed a thirdmarriage. He gol the grace and married Eudocia Baiane, his third wife. Butshe soon died, too. Longing for a son who can be his inheritor, Leon gotmarried for the fourth time. But now the priest who acted in the wedding wasremoved and the emperor was punished: he could no longer gel into the hollyplaces. After Leon' s death, his wife was cast out. There was di vis ion betweenthe priests and reprisals against !hose who hadjustified the fourth marriage.The authoress shows in an annex four Leon's laws related to marriage.